Implementasi Model Creative Problem Solving (CPS) Pada Smart Mobile Cloud Learning System Multimedia Berbasis Animasi Untuk Meningkatkan Kemampuan Berfikir Kreatif Siswa - Wahyudin Sanusi; Erlangga Erlangga; Dela Adelia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Creative thinking skills are skills that need to be developed for all students, and creativethinking is often associated with problem solving activities. Students who have the ability to thinkcreatively use all their thinking skills to find solutions to the problems they face. However, thecurrent learning process has not fully developed students' creative thinking skills. This is inaccordance with a preliminary study by researchers that teachers show that in the learning process to manage network infrastructure, teachers have not developed creative thinking skills due to the high demand for teaching materials. So this study aims to design a smart mobile cloud learning multimedia system based on animation with a Creative Problem Solving model to improve students' creative thinking skills. The research method is quantitative, using a Pre-Experimental Design research design, namely One-Group Pretest-Posttest. The multimedia development method refers to the Whole Life Cycle (SHM) method. The results of this survey: 1) Multimedia is available, the average percentage of media professionals is 86.68, and the category is “very good”. 2) Multimedia design can improve students' creative thinking skills. This refers to the four indicators of creative thinking, namely the average creative thinking ability of students as a whole or 55.12 in the